(untitled) (Global Journal of Human-Social Science, 2023)
Prisoner women are subjects of human rights therefore they are holders of them and the Mexican State is obligated to guarantee it however the right to education as a way to achieve social reintegration suffers from structural and historical discrimination by the penitentiary system which discriminates the intellectual development of prisoner women since the policies of the penitentiary centers regarding the education of prisoner women is to provide them with stereotyped activities such as Beauty crafts and sewing With this type of education they submit and enslave women to the patriarchal system which not allow them to advance in their intellectual development